2021
DOI: 10.1111/jcpt.13572
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the relationship between dapagliflozin and loss of weight in type 1 diabetes mellitus patients

Abstract: What is known and objectives: Dapagliflozin was the first oral treatment approved in type 1 diabetes mellitus (T1DM) patients, simultaneously improving body weight.However, the time course and dose effect of dapagliflozin on loss of weight in T1DM patients was still unknown. The present study aimed to investigate quantitative relationship between dapagliflozin and loss of weight in T1DM patients based on Modelbased Meta-analysis.Methods: Five dapagliflozin dosage groups, two of them were 5 mg/day and three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In addition, the duration of dapagliflozin treatment was from 12 to 52 weeks, the age of T1DM patients were in the range of 41.9–55.0 years, the baseline value of HbA1c ranged from 7.40 to 8.53%, the duration of T1DM ranged from 18.98 to 30 years, and the total baseline insulin dose was in the range of 44.7–63.1 IU, which are shown in the Supplementary Data. Part of the literature information was retrieved from the previous study ( Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the duration of dapagliflozin treatment was from 12 to 52 weeks, the age of T1DM patients were in the range of 41.9–55.0 years, the baseline value of HbA1c ranged from 7.40 to 8.53%, the duration of T1DM ranged from 18.98 to 30 years, and the total baseline insulin dose was in the range of 44.7–63.1 IU, which are shown in the Supplementary Data. Part of the literature information was retrieved from the previous study ( Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The actual efficacy curve of dapagliflozin on HbA1c from the final model was simulated using the Monte Carlo method, which was a mathematical technique used to predict the situation in which an event would occur ( Wang et al, 2021 ; Wang et al, 2022 ). The actual maximal efficacy (AE max ) of dapagliflozin on HbA1c and the dapagliflozin therapeutic effect on HbA1c after reaching AE max when continued for 0.5 and 1 year were simulated.…”
Section: Methodsmentioning
confidence: 99%
“…E max were often used to describe E max efficacy curve. 12,31,32 In addition, the sirolimus dosage was flexible and adjusted according to drug concentration, where the intersection of sirolimus concentration range included in this study was about 8-10 ng/ml. Therefore, in order to However, this study also had limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, E max model was selected for machine learning, where the evaluation indicator was the change rate of SLEDAI from baseline value. A total 103 patients with SLE were included for modelling, among which the E max , ET 50 were −53.9%, 1.53 months in the final model, respectively, and further simulation found that the follow‐up time to achieve 25%, 50%, 75% and 80% (plateau) E max of sirolimus effecting on disease activity in patients with SLE were 0.51, 1.53, 4.59 and 6.12 months, respectively, among which 25%, 50%, 75% and 80% E max were often used to describe E max efficacy curve 12,31,32 . In addition, the sirolimus dosage was flexible and adjusted according to drug concentration, where the intersection of sirolimus concentration range included in this study was about 8–10 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in order to acquire the actual effect of carnitine supplementation on body weight in patients with PCOS, the control effect needs to be removed from the sum effect. Certainly, this method had been applied in many previous studies ( 50 , 51 ). Through this scheme, the influence of different diets in different studies could be eliminated.…”
Section: Discussionmentioning
confidence: 99%